Role of Central Nervous System Circuits in Promotion of Breast Cancer Progression by Depression - Yingchao WU; Yuqi LIANG; Qian ZUO; Qianjun CHEN (Zhongliu Fangzhi Yanjiu)
With the development of neuroscience and oncology, the direct regulation effect of central nervous system circuits on tumors has been gradually revealed. Evidence indicates that the therapy targeting emotion-related encephalic regions may have great potential in blocking the promotion of breast cancer progression by depression. The underlying complex mechanisms involve the generation of depression and the regulation of tumors by central nervous system circuits. However, a systematic summary is lacking in this field. This article reviews the latest research progress of the central nervous system circuits and the generation of depression, the neural connection between the central nervous system and peripheral tumor, and the regulation of the tumor immune microenvironment by the sympathetic nervous system. It also systematically investigates the potential mechanism of the central nervous system circuit in the promotion of breast cancer progression by depression to establish new solutions for the comprehensive treatment of breast cancer.